2019
DOI: 10.1186/s12890-019-0994-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences at presentation of idiopathic pulmonary fibrosis in Sweden

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a disease with poor prognosis mainly affecting males. Differences in clinical presentation between genders may be important both for the diagnostic work-up and for follow-up. In the present study, we therefore explored potential gender differences at presentation in a Swedish cohort of IPF-patients.MethodsWe studied patients included in the Swedish IPF- registry over a three-year period from its launch in 2014. A cross-sectional analysis was performed for data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
11
12
0
Order By: Relevance
“…Thus, approximately 65% of the patients received anti-fibrotic treatment in our study, which is considerably more than in Germany (44%) [ 9 ], Finland (26%) [ 10 ], and Australia (23%) [ 6 ]. The present study shows that patients on anti-fibrotic therapy appear to survive longer than untreated patients, a result similar to what other registries have reported [ 6 , 8 , 20 ]. In order to avoid a potential bias in mortality analysis, we showed that there were no significant differences in baseline lung function between anti-fibrotic treated and untreated groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, approximately 65% of the patients received anti-fibrotic treatment in our study, which is considerably more than in Germany (44%) [ 9 ], Finland (26%) [ 10 ], and Australia (23%) [ 6 ]. The present study shows that patients on anti-fibrotic therapy appear to survive longer than untreated patients, a result similar to what other registries have reported [ 6 , 8 , 20 ]. In order to avoid a potential bias in mortality analysis, we showed that there were no significant differences in baseline lung function between anti-fibrotic treated and untreated groups.…”
Section: Discussionsupporting
confidence: 92%
“…The Swedish IPF Registry (SIPFR) is a nationwide registry collecting comprehensive longitudinal data of IPF patients and implemented in 22 respiratory medicine units across Sweden [ 13 , 19 , 20 ]. The SIPFR also includes patients diagnosed before the registry was launched in 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of our patients who developed COVID-associated ILD were males, which has also been previously reported in literature with certain ILDs like idiopathic pulmonary brosis [13,14]. COVID associated brosis is one of the lung insults already described with previous Coronavirus infections [2,3], and there are emerging studies now reporting COVID-19 associated early pulmonary brosis.…”
Section: Discussionsupporting
confidence: 81%
“…Other substantial respiratory outcomes are also associated with smoke exposure, though evidence is more limited. For example, percent of predicted forced vital capacity (FVC%) and percent of predicted total lung capacity (TLC%) were lower in males compared to females in a study of idiopathic pulmonary fibrosis (IPF) in Sweden (Kalafatis et al 2019 ). When smoking history was considered, male ex-smokers showed lower FVC%, TLC%, and percent of predicted diffusing capacity for carbon monoxide (DLCO%), compared to female ex-smokers.…”
Section: Exposure-related Sex-biased Respiratory Diseasesmentioning
confidence: 99%